Digitalisasi Pertanian melalui Program Kostratani pada Agribisnis Padi Sawah di Kecamatan Barebbo Kabupaten Bone - Rafika Dewi Pratiwi; Darmawan Salman; Imam Mujahidin Fahmid (Jurnal Sosial Ekonomi Pertanian, 2022)
Kostratani or Agricultural Strategic Command is the center of agricultural development activities at the sub-district level to optimize the tasks, functions, and roles of the Agricultural Extension Center (BPP) by utilizing and maximizing IT functions to realize national food sovereignty. With the existence of Kostratani, it is hoped that the Ministry of Agriculture can have a database that is truly accurate and not only increases production and quality, but also improves farmers' welfare through empowering extension workers at BPP. BPP Barebbo is one of the BPP Kostratani models under the guidance of the Agricultural Development Polytechnic (Polbangtan) of Gowa. BPP Barebbo is located in Kampuno Village, Barebbo District, Bone Regency, South Sulawesi Province. This study aims to determine and obtain an overview of the implementation of Kostratani and the benefits received by recipients of lowland rice agribusiness services in Barebbo District. This research was conducted in February-April 2022 at BPP Barebbo, Bone Regency. The basic method of this research is a case study with a qualitative approach. The informants of this research were the BPP Coordinator, agricultural extension workers, and farmers. Research data obtained by interview and observation. Data were analyzed qualitatively without statistical tests. The results show that BPP Barebbo has implemented the functions and roles of BPP Kostratani but there are still recipients of rice agribusiness services who have not felt the benefits, namely the downstream system. It is hoped that BPP Barebbo can maintain its implementation and increase the benefits that can be received by rice farmers.